Effect of time and temperature on the functional and textural characteristics of starch isolated, from pigmented traditional rice cultivars of Kashmir - Bhat, Farhan Mohiuddin; Riar, Charanjit Singh; Sommano, Sarana Rose (Journal of Postharvest Technology, 2024)
The research was to done to determine the effect of amylose content, temperature and time periods on the functional, textural and rheological  properties of starch isolated from five different rice cultivars. The water solubility and swelling power was found to increase with every 10oC  increase in temperature with Samarkand exhibiting highest values of water solubility. The syneresis between starches of different rice cultivars  during storage showed a significant difference with starch gel of Shel Kew exhibiting highest syneresis ranging from 16.715 to 4.873 % during  storage period of 120h. The turbidity values estimated from gelatinized starch suspensions from different rice cultivars was found to increase  progressively during the storage periods. The fluctuating trends in turbidity values of starches from Gull zag and Kaw kareed could be  attributed to the amylose aggregation and crystallization that are not completed during first 4 days of during storage periods. The texture  profile analysis of starch gels of the analysed rice cultivars revealed a significant difference in their textural characteristics with Kaw kareed exhibiting the highest value of hardness, gumminess and chewiness. The rheological analysis revealed that starch of Gull zag was found to  depict the highest peaks values of G/ (7550Pa) and G// (630Pa).
Keywords: Rice starch; amylose content; syneresis; turbidity; TPA; rheological characteristics